Occupational Health Perspective on Upper-Extremity Musculoskeletal Disorders among Traditional “Batik” “Canting” Workers: A Cross-Sectional Study - Diki Bima Prasetio; Eli Sahiroh; Nasya Adelia Putri; Shinta Dwi Surya Pramesti; Sri Lestari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Musculoskeletal Disorders (MSDs) are chronic health issues frequently experienced by batik workers due to discrepancies between workstation design and anthropometric principles. The process of canting (hand-waxing) involves static postures and repetitive movements that trigger muscle tissue ischemia and lactic acid accumulation. This study aims to identify MSDs complaints in the upper extremities specifically the shoulders, elbows, and wrists hand and analyze the contributing risk factors. This observational study utilized a cross-sectional design involving 166 batik workers in Jarum Village, Klaten. Data were collected through individual characteristic questionnaires (age, years of service, and daily work duration) and the Nordic Body Map (NBM) adopted from the Standardised Nordic questionnaires for the analysis of musculoskeletal symptoms. Data analysis was performed using the Chi-Square test to determine the significance of relationships between variables. The findings indicate that the majority of respondents were aged 45–64 years (59%) with a daily work duration of ≥ 8 hours (56.6%). There was a statistically significant assosiation between age and years of service with wrist-hand pain. The 45–64 age group reported the highest prevalence of wrist pain, reaching 92.9%. Age and years of service are significantly associated with upper extremity musculoskeletal complaints, particularly in the wrist and hand, among batik workers. Ergonomic engineering interventions are necessary to mitigate the risk of injury resulting from poor working postures during the batik-making process.